An Analysis Types of Slang Words Found in Green Day “Jesus of Suburbia” Song Lyrics - Arbhawa, I Komang; Santika, I dewa Ayu Devi Maharani (Institut Agama Islam Negeri Palopo, 2024)
Slang is one of the variations of social language that grows in society. The use of slang among teenagers in informal situations functions as a form of self-identification with other individuals. This study analyzes the types of slang words found in the lyrics of the song Jesus of Suburbia on the Green Day album. The method used in this study is a qualitative descriptive method and the technique used is an observation technique by listening to the song repeatedly, noting all the slang words in the song, collecting all the data. The theory used is in Kipfer and Chapman (2007). This study concludes that the types of slang words found in the lyrics of Green Day songs are primary and secondary slang words. The following are the results of the study, there are 5 primary slang words and 6 secondary slang words in the lyrics of the song Jesus of Suburbia on the Green Day album.